The vascular microenvironment and its stem cells regulate vascular homeostasis - Wang, Yanhui; Zhang, Xiaoyun; Li, Xin; Cheng, Min; Cui, Xiaodong (Frontiers in Cell and Developmental Biology, 2025)
The vascular microenvironment comprises of anatomical structures, extracellular matrix components, and various cell populations, which play a crucial role in regulating vascular homeostasis and influencing vascular structure and function. Under physiological conditions, intrinsic regulation of the vascular microenvironment is required to sustain vascular homeostasis. In contrast, under pathological conditions, alterations to this microenvironment lead to vascular injury and pathological remodeling. According to the anatomy, the vascular microenvironment can be subdivided into three sections from the inside out. The vascular endothelial microenvironment, centered on vascular endothelial cells (VECs), includes the extracellular matrix and various vascular physicochemical factors. The VECs interact with vascular physicochemical factors to regulate the function of various parenchymal cells, including hepatocytes, neurons and tumor cells. The vascular wall microenvironment, comprising the vasa vasorum and their unique stem/progenitor cell niches, plays a pivotal role in vascular inflammation and pathological remodeling. Additionally, the perivascular microenvironment, which includes perivascular adipose tissue, consists of adipocytes and stem cells, which contribute to the pathological processes of atherosclerosis. It is anticipated that targeted regulation of the vascular microenvironment will emerge as a novel approach for the treatment of various diseases. Accordingly, this review will examine the structure of the vascular microenvironment, the regulation of vascular function by vascular cells and stem/progenitor cells, and the role of the vascular microenvironment in regulating cardiovascular diseases.